FACTORS INFLUENCING UTILIZATION OF LONG-ACTING REVERSIBLE CONTRACEPTIVES AMONG WOMEN AGED 15-45 YEARS IN VURRA HEALTH CENTER 111 ARUA DISTRICT. A CROSS-SECTIONAL STUDY. - NELSON AYIKOBUA; Mulodokayi Richard Niwagira (Student's Journal of Health Research, 2023)
Introduction:  This study aimed to explore the factors influencing the utilization of long-acting reversible contraceptives (LARCs) among women aged 18-45 years in Vurra Health Centre III, Arua District. The main factors influencing the utilization of LARCs were knowledge about LARCs, attitude toward family planning, and accessibility of LARCs. Objective: The Purpose of the study, was to assess the prevalence and factors influencing the utilization of long-acting reversible contraceptives among women of reproductive age. Methodology:  The study utilized a cross-sectional design, and data was collected through a structured questionnaire administered to 60 women attending health services such as family planning at Vurra Health Centre III. The questionnaires were submitted by a well-trained research assistant. Results:  The study found that the utilization of LARCs among women in Vurra Health Centre III was low. The study also found that the level of education was 30.2%, the desire to conceive shortly 38.33%, and misconceptions 31.47%. Conclusion:  A majority of the participants were utilizing LARC particularly injectables and implants, especially married women. This study showed that women having five or more children were more likely to use LARC methods. Recommendations:  The study recommends that health education and awareness campaigns should be intensified to increase knowledge and awareness of LARCs, and the availability and accessibility of LARCs should be improved to increase their uptake among women in Vurra Health Centre III, Arua District.